BUSANA ISLAMI SEBAGAI PRAKTIK RELIGIUS DAN FENOMENA SOSIAL DALAM KEHIDUPAN MODERN - Aslama, Sadida; Utami, Titania Putri; Muzhafaroh, Tsaqifa (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study discusses the symbolic meaning of the hijab within the context of Islamic clothing in Indonesia, examining whether the hijab truly represents an individual's level of piety or is rather a product of social construction. The research employs a qualitative-descriptive approach through literature analysis and observation of social phenomena. Findings reveal that the hijab functions not only as a symbol of religious obedience but also as a part of social identity, lifestyle, and commodification within the modern fashion industry. The phenomenon of the mini hijab widely used in campuses and the influential role of social media demonstrate a negotiation of meanings between religious values and popular culture demands. From the perspective of Shafi'i fiqh, the mini hijab does not fulfill the sharia requirements as proper aurat covering, thus the interpretation of the hijab as a symbol of piety should also consider the inner sincerity and behavior consistent with Islamic teachings.